Comparison of landuse and landcover changes, drivers and impacts for a moisture-sufficient and drought-prone region in the Ethiopian highlands - Ali, H.; Descheemaeker, Katrien K.; Steenhuis, Tammo S.; Pandey, S. (Cambridge University Press, 2011)
Land use and land cover changes are driven by human actions and, in turn, drive changes that alter the availability of products and services for people and livestock. For proper planning, these cause-and-effect interrelations need to be understood. This is especially important for Ethiopia where the resource base is declining and should be improved in order to feed the growing population. To better understand these interrelations,we studied trends in the natural resource base over a 35-year period for two contrasting sites in the Ethiopian Highlands: semi-arid and water-short Lenche Dima, and sub-humid and moisture-sufficient Kuhar Michael. Information was obtained using time-series satellite images, geographical positioning system, a socio-economic survey and a document review. Results showed that for sub-arid Lenche Dima there were minimal changes in land use and land cover patterns, while in water-sufficient Kuhar Michael cropland greatly increased at the expense of the grazing land and bare soil. At the same time land holding size and cattle numbers decreased in Lenche Dima while they remained the same in Kuhar Michael, although overall land holdings remained larger in Lenche Dima than in Kuhar Michael. This study thus found large differences in development of agriculture since the 1970s: intensification of agriculture is possible in the water-sufficient sub-humid climate by displacing animal husbandry with high value crops that need irrigation during the dry monsoon season. This is not possible for the semi-arid area where water is the limiting factor in production even if a market is close by. Agriculture in the semi-arid areas also requires larger land holdings because of the risk of droughts and low yields during some years. This comparative analysis suggests that without sufficient water, the shift from subsistent to commercial market-driven agriculture cannot be easily accomplished.